Aplikasi Probiotik Probio One dengan Dosis yang Berbeda pada Pakan Ikan Nila - Ni Made Ayuk Suardani; Gde Raka Angga Kartika; Hardiansyah Bama Saputra (Current Trends in Aquatic Science, 2023)
Various efforts have been made by the community to improve the quality and further accelerate the growth of nile fish. One of them is by mixing probiotics into fish feed. The probiotic used is probio one probiotic which is usually given to koi fish. This study was conducted to find out how the growth of tilapia given feed mixed with probiotics with different doses. The study was conducted with treatment A as a control, treatment B using a probiotic dose of 2,5 g/kg feed, treatment C using a probiotic dose of 5 g/kg feed, treatment D using a dose of 7,5 g/kg feed and treatment E of 10 g/kg feed. This research was conducted over a period of 40 days. Water quality parameters measured in this study included pH, temperature and DO as well as observations of fish growth in the form of absolute weight, specific growth rate (SGR), survival rate and feed conversion ratio. Growth observations were analyzed using One Way Analysis of Variance (ANOVA) and a follow-up test in the form of Duncan's Test. The results showed that the treatment using a dose of 7,5 g/kg feed gave a significantly different effect on absolute weight, specific growth rate and survival rate of tilapia. The water quality parameters measured included pH in the range of 7,98-8,20 while DO in the range of 6,8 â€“ 8,4 mg/L and temperature in the range of 26,64 -26,90Â°C.